Optical soliton: Review of its discovery and applications in ultra-high-speed communications - Hasegawa, Akira (Frontiers in Physics, 2022)
This paper reviews the discovery of the optical soliton and historical attempts of its applications for ultra-high speed communications. It also reveals various episodes that took place in the course of its discovery and in subsequent developments in the form of a memoir. The paper is expected to stimulate young scientists for their future activities and contributions.